The Meaning of Ma'parapa' Speech in Wedding Ceremonies and its Implications on Ethnopedagogic Values at Elementary School - Rosminati Rampo; Bethin Simega; Rita Tanduk (Universitas Islam Negeri Palopo, 2025)
This study aims to examine the meaning contained in the ma' parapa' utterance in the traditional wedding ceremony of the North Toraja community, as well as its application to ethnopedagogical values in the context of learning at SDN 3 Rantepao. The ma'parapa' utterance is part of an oral tradition that is full of cultural, moral, social, and educational values that have the potential to be an open source in ethnopedagogy-based character education. The method used in this study is a qualitative method with a semiotic approach. Data were obtained through participatory observation, in-depth interviews with traditional leaders (To minaa), teachers, and the community, as well as documentation of the ma' parapa' text. The results of the study indicate that the ma' parapa' utterance contains ethical and educational messages such as values of respect for parents, honesty, responsibility, togetherness, and religious values, all of which are relevant to the development of character education in schools. The implications of the research results indicate that these values can be integrated into thematic learning and local content in elementary schools in order to instill local cultural values from an early age. This study recommends the development of local culture-based teaching materials, teacher training, and cultural preservation programs involving the school community.